Kontradiksi Pemahaman Hadis Nabi mengenai Khurafat, Takhayul, dan Bid’ah: Studi Kitab Mafahim Yajibu an-Thussohah Karya Abuya Sayyid ‘Alawi al-Maliki - Khilda Minhatul Maula; Anisatun Muthi’ah; Nurkholidah Nurkholidah; Ahmad Lutfi; Anwar Sanusi (Gunung Djati Conference Series, 2023)
This study aims to discuss the contradictions in the understanding of hadith regarding khurafat, takhayul, and bid'ah in the book Mafahim Yajibu an-Thussohah by Abuya Sayyid 'Alawi al-Maliki. This study uses a qualitative approach by applying the descriptive-analytical method. The results and discussion of this study indicate that basically, Muslims do not have divisions due to openness or tolerance among people, but understanding the texts of the Prophet's hadith requires an accurate methodology because if the procedure is ignored, a verdict of bid'ah usually results. This study in general concludes that the contradictions in the understanding of hadith regarding khurafat, takhayul, and bid'ah have a big impact if one understands carefully which part of 'amaliyah (deeds) is said to destroy one's actions.